2017
DOI: 10.5005/jp-journals-10062-0007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Caries among Elementary School Girls in Riyadh, Kingdom of Saudi Arabia: A Cross-sectional Survey

Abstract: Aim: To assess caries prevalence among 6-to 9-year-old female children in Riyadh, Kingdom of Saudi Arabia and compare between results based on nationality and age levels. Materials and methods:A total of 17,891 female students from 120 public female elementary schools in Riyadh city were examined according to the World Health Organization (WHO) diagnostic criteria. The decayed [dt], missing due to caries [mt], and filled [ft] primary teeth (dmft) index and its components were measured. One-way analysis of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Although the sample size was only modest, the surveyed children should be relatively representative of Saudi children with primary dentition. Various studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] reported on dmft in Arabian children; among these studies, few researchers focused only on primary dentition [ 19 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], and some concentrated on both primary and permanent dentitions [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 34 , 35 , 36 ]. The reported prevalence of carious in primary teeth ranges from 57.2% to 91.2% from previously reported studies in the literature [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , ...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the sample size was only modest, the surveyed children should be relatively representative of Saudi children with primary dentition. Various studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] reported on dmft in Arabian children; among these studies, few researchers focused only on primary dentition [ 19 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], and some concentrated on both primary and permanent dentitions [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 34 , 35 , 36 ]. The reported prevalence of carious in primary teeth ranges from 57.2% to 91.2% from previously reported studies in the literature [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , ...…”
Section: Discussionmentioning
confidence: 99%
“…Another two studies [ 29 , 30 ] from Jeddah reported a higher prevalence of dental caries compared to the present study in both sexes, 83.4% and 87.1%, respectively. Alshiha et al [ 32 ] reported an 85.5% caries prevalence among 6183 female subjects of 6–7 years from the Riyadh region. Consequently, another study reported an almost similar prevalence (83%) in 578 male children from the Riyadh region of 6.92 years mean age [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This difference is understandable as well-off families are more likely to invest on appearances and aesthetics. A study conducted on school going children in Saudi Arabia found that the mean DMFT score among children aged 5-12 year old was 3.85 [36].…”
Section: Discussionmentioning
confidence: 99%
“…Recently a study on a large sample (17,891) of Riyadh 7-9-year-old female students revealed a high (88.8%) caries prevalence (Alshiha et al, 2017). Presence of hypo-mineralization and caries in the same tooth might affect the proper diagnosis of enamel breakdown whether it is actually due to caries or hypo-mineralization or a combination of both.…”
Section: Discussion:-mentioning
confidence: 99%